2020
DOI: 10.1101/2020.07.17.209288
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SARS-CoV-2 Spike protein co-opts VEGF-A/Neuropilin-1 receptor signaling to induce analgesia

Abstract: Global spread of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) continues unabated. Binding of SARS-CoV-2's Spike protein to host angiotensin converting enzyme 2 triggers viral entry, but other proteins may participate, including neuropilin-1 receptor (NRP-1). As both Spike protein and vascular endothelial growth factor-A (VEGF-A) - a pro-nociceptive and angiogenic factor, bind NRP-1, we tested if Spike could block VEGF-A/NRP-1 signaling. VEGF-A-triggered sensory neuronal firing was blocked by Sp… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
52
0
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(56 citation statements)
references
References 70 publications
(85 reference statements)
0
52
0
4
Order By: Relevance
“…In addition, NRP1 is up-regulated in clinical tumor samples (72). Recent studies also indicate that SARS-CoV-2 spike protein can also bind NRP1 in pulmonary vagal neurons, blocking nociceptive signaling and thereby potentially contributing to "asymptomatic" virus spread (73). Our data demonstrate that COUP-TF2 drives NRP1 expression, facilitating lung vascular repair, although the body of literature suggests that COUP-TF2-mediated NRP1 signaling may promote pathologic angiogenesis in other lung disease contexts, possibly pulmonary hypertension or lung tumor angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, NRP1 is up-regulated in clinical tumor samples (72). Recent studies also indicate that SARS-CoV-2 spike protein can also bind NRP1 in pulmonary vagal neurons, blocking nociceptive signaling and thereby potentially contributing to "asymptomatic" virus spread (73). Our data demonstrate that COUP-TF2 drives NRP1 expression, facilitating lung vascular repair, although the body of literature suggests that COUP-TF2-mediated NRP1 signaling may promote pathologic angiogenesis in other lung disease contexts, possibly pulmonary hypertension or lung tumor angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…What is crucial here is to understand the molecular basis that allows for such disruption to ACE2 to occur and investigate whether synthetic NPs could cause similar effects on certain proteins? Moreover, there is a growing evidence that the SARS-CoV-2 can cause analgesia through its effects on the VEGF-A/Neuropilin-1 receptor signaling pathway (Moutal et al, 2020). It was found that SARS-CoV-2 not only binds to ACE2 protein but also to neuropilin-1, which is a transmembrane glycoprotein highly expressed in the respiratory and olfactory epithelium, vasculature and has several roles within the nervous system (Cantuti-Castelvetri et al, 2020).…”
Section: Trafficking Of Sars-cov2 Within Cellsmentioning
confidence: 99%
“…These connections raise an interesting question: does interference with the VEGF-A/NRP-1 signaling pathway by SARS-CoV-2 result in dampened pain? This question has been examined by our laboratory; we recently showed that SARS-CoV-2 Spike protein binding to NRP-1 prevents VEGF-A signaling and reduces neuropathic pain in an animal model 27 . Thus, NRP-1 represents a novel target for treating neuropathic pain 27 .…”
Section: Introductionmentioning
confidence: 99%
“…This question has been examined by our laboratory; we recently showed that SARS-CoV-2 Spike protein binding to NRP-1 prevents VEGF-A signaling and reduces neuropathic pain in an animal model 27 . Thus, NRP-1 represents a novel target for treating neuropathic pain 27 . Furthermore, targeting NRP-1 also presents a unique approach to inhibiting viral entry and/or re-entry into cells to reduce viral load.…”
Section: Introductionmentioning
confidence: 99%